2020
DOI: 10.1002/adfm.202003777
|View full text |Cite
|
Sign up to set email alerts
|

Transient Support from Fibroblasts is Sufficient to Drive Functional Vascularization in Engineered Tissues

Abstract: Formation of capillary blood vasculature is a critical requirement for native as well as engineered organs and can be induced in vitro by coculturing endothelial cells with fibroblasts. However, whether these fibroblasts are required only in the initial morphogenesis of endothelial cells or needed throughout is unknown, and the ability to remove these stromal cells after assembly can be useful for clinical translation. In this study, a technique termed CAMEO (Controlled Apoptosis in Multicellular Tissues for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 73 publications
(88 reference statements)
0
43
0
Order By: Relevance
“…1 in the supplementary material ). Previous work has shown that similar vasculogenic tissues do get stiffer over time, 8,12 with this increasing stiffness dependent largely on the presence of fibroblasts within the tissue. 8 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…1 in the supplementary material ). Previous work has shown that similar vasculogenic tissues do get stiffer over time, 8,12 with this increasing stiffness dependent largely on the presence of fibroblasts within the tissue. 8 …”
Section: Resultsmentioning
confidence: 94%
“…1(a) ] with an approximate tissue thickness of 0.5 mm. The PDMS mold used in this study was adapted from a previously published platform 8 to enable the formation of vascular networks without fluid flow and to allow for tissue injury by uncovering the central gel region. We utilized a composite gel of 0.4 mg/ml collagen I and 2.5 mg/ml fibrinogen because these composite gels have been shown to retain the robust vasculogenesis, which is observed in pure fibrin gels, 10 while also incorporating collagen I, a fibrous matrix molecule that imparts strength to mature tissue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 98 ] In contrast to the EC cell lining technique, vasculogenesis and angiogenesis‐based methods can be combined with advanced microfluidic‐based techniques to recreate 3D microvascular networks that can be adapted into organ‐on‐a‐chip platforms. [ 99–105 ] A tri‐culture of human bone marrow mesenchymal stem cells (hBM‐MSCs), osteogenically differentiated (OD) hBM‐MSCs, and human umbilical vein endothelial cells (HUVECs) embedded in 2.5 mg mL −1 fibrin gel were used to recreate the bone microvasculature. [ 106 ] Experimental results showed the formation of functional microvascular networks after 4 days.…”
Section: Bone Vasculature and Innervation On‐a‐chipmentioning
confidence: 99%